Homomorphic detection of convolved signals using class 1 filters - Lindquist, C.S.; Cox, S.W. (Thirty-Fourth Midwest Symposium on Circuits and Systems, 1991, 1991)
It is shown that signals which are convolutionally combined can be detected using optimal homomorphic filtering. The system uses Fourier transforms combined with a log( ) operator. Dual-channel filtering is described. Single-channel filtering is also possible but does not perform as well. A simulation is presented to demonstrate the computations involved. Although Class 1 algorithms were used for simplicity, the techniques have been extended using Class 2 algorithms. Excellent results are also obtained. This homomorphic filtering technique can be used to solve a variety of problems that cannot otherwise be solved using classical methods.< >